The Soft Touch: How postharvest handling affects the quality and shelf-life of sweetpotato roots - International Potato Center (2016)
Across Kenya, supermarket customers are now buying delicious golden bread made with vitamin A boosting orange-fleshed sweetpotato (OFSP) purée. To meet this demand, a year-round supply of fresh sweetpotato roots is required, and can be achieved through a combination of staggered production and the storage of fresh OFSP roots to cover periods of low supply. However, careful postharvest handling is required to optimise the quality and shelf-life of these roots.